Good Wishes in Advertisements in Turkish and Bosnian Languages - Bakšić, Sabina (Prilozi za orijentalnu filologiju, 2017)
This paper presents an anylisis of good wishes in advertisements in Turkish and Bosnian. Methodologicaly, three theoretical approach are combined: a pragmatic approach, in particular Penelope Brown and Stephen C. Levinson’s model of politeness strategies, cognitive-linguistic approach and social semiotic approach. The analysis shows ambiguity in these advertisements. According to their form they are good wishes but in fact they are directives whose illocution is to force addressee to buy the product of addressers. These advertisements also represent one of the constants in advertisements – their structure, which mainly corresponds to the Desire – Arousal-Fulfilment and Problem – Solution pattern of the text.